The impact of direct foreign and local investment on indigenous communities in East Africa: a case study of the Maasai of Kenya and Tanzania - Alejandro, Lorite (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2007.